2014
DOI: 10.1149/2.0131407ssl
|View full text |Cite
|
Sign up to set email alerts
|

Formation of ITO Nanowires Using Conventional Magnetron Sputtering

Abstract: ITO nanowires could be grown in oxygen-free Ar sputtering gas directly after the formation of ITO films with thicknesses of 10-50 nm using conventional magnetron sputtering. Growth of nanorods occurred at substrate temperatures of about 100 • C and higher, whereas nanowires with lengths of 1-10 μm and diameters of roughly 20-200 nm were formed at about 175 • C and above. The diameter, length and density of the nanowires could be controlled by varying the sputtering time, substrate temperature, and SnO 2 conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The first one requires relatively high growth temperatures, normally ranged between 700–1000 °C. The second one needs relatively low growth temperatures: from 250 to 600 °C [ 44 , 45 , 46 ]. Within the frame of the self—catalytic mechanism, the binary phase diagram of the In–Sn system [ 4 , 47 ] presents a eutectic point located near 125 °C.…”
Section: Growth Of Ito Nanowires Characteristics and Dependencesmentioning
confidence: 99%
“…The first one requires relatively high growth temperatures, normally ranged between 700–1000 °C. The second one needs relatively low growth temperatures: from 250 to 600 °C [ 44 , 45 , 46 ]. Within the frame of the self—catalytic mechanism, the binary phase diagram of the In–Sn system [ 4 , 47 ] presents a eutectic point located near 125 °C.…”
Section: Growth Of Ito Nanowires Characteristics and Dependencesmentioning
confidence: 99%
“…Many methods have been tried to obtain ITO nanostructures, such as sputtering, thermal evaporation, and electron beam evaporation [14][15][16]. Among all of these methods, magnetron sputtering is the best choice, because of the faster deposition rate, better film quality, and the more stable repeatability [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is inferred that the conductivity of this film is a crystal defect derived from the film structure itself. In 1968, Philip found that the doping of Sn ions in the indium oxide film enhanced the conductivity of the overall film, and then produced In 2 O 3 :Sn film [ 7 ], now widely consolidated in indium tin oxide [ 8 , 9 , 10 ] applications.…”
Section: Introductionmentioning
confidence: 99%